Peningkatkan Kemampuan Kognitif Anak Usia Dini Dalam Mengenal Huruf Melalui Media Sandpaper Letters - Indahilma Mubarokah; Abdul Baits; Teti Sumiati; Sopa Samrotul Fuadah; Ai Paridah (Journal on Education, 2024)
The process of introducing letters to early childhood must be done through activities or using concrete media. One of the concrete learning media that can be used by early childhood to recognize letters is using Sandpaper Letters media. This study aims to: 1) Determine the preparation of the Daily Learning Implementation Plan (RPPH) used to improve the cognitive abilities of early childhood in recognizing letters through Sandpaper Letters media; 2) Determine the implementation of efforts to improve the cognitive abilities of early childhood in recognizing letters through Sandpaper Letters media; 3) Determine the results of improving the cognitive abilities of early childhood in recognizing letters through Sandpaper Letters media or Raba Letters in Group B Kober Nuurul Qur'an, Indihiang District, Tasikmalaya City. This study is a Classroom Action Research model Kurt Lewin. The subjects in this study were Group B students totaling 10 students, consisting of 7 male students and 3 female students. Data collection techniques were observation, interviews and documentation. The results of the study showed that: First, cycle I, the preparation of RPPH was classified as moderate, with an average of 2.85, cycle II the preparation of RPPH was classified as very good, obtained an average of 3.70. Second, the implementation of learning in cycle I, obtained an average of 2.81 with moderate qualifications, cycle II, an average score of 3.33 with good qualifications. Third, the results of the study in cycle I were 50% of all students, 5 students were still in the Not Developing (BB) category, 3 students had Started to Develop (MB), and 2 students had Developed According to Expectations (BSH). While in cycle II, 80% of all students, 2 students were still in the Not Developing (BB) category, 4 students had Started to Develop (MB), 2 students had Developed According to Expectations (BSH), and 2 students had Developed Very Well (BSB).